Women’s perceptions and preferences toward HPV self-sampling in France: A questionnaire within the French CapU4 Trial - Hélène De Pauw; Alexandra Ducancelle; Marc Arbyn; Adeline Pivert; Anne-Sophie Le Duc Banaszuk; Juliette Noyelle; Johane Le Goff; Franck Rexand-Galais; Gilbert Donders; Caroline Lefeuvre (Journal of Infection and Public Health)
Background: Despite organised screening efforts since 2018 targeting under-screened women, cervical cancer (CC) screening coverage remains moderate (60 %) in France. The target age for HPV-based screening is women aged 30–65. Vaginal self-sampling (VSS) has recently been introduced for women who have not been screened. This study assesses women’s perceptions and preferences toward HPV self-sampling among women enrolled in the CapU4 trial. Methods: CapU4 is a randomised controlled trial with two experimental arms (mailing either a urine self-sampling (USS) or VSS kit) and a control arm (mailing of a conventional invitation letter). The trial invited 15,000 women aged 30–65, who had no screening test recorded since more than four years and who did not respond to an invitation letter within 12 months before. Half of the women in each arm were randomly selected to receive a supplementary questionnaire (sent in March 2023, with responses collected until August 2023). Results: In total, 682 completed questionnaires were analysed (9.1 % response rate). Most women found self-sampling instructions clear (VSS 87.4 %, USS 90.7 %) and procedures easy (VSS 85.9 %, USS 90.3 %). About 23.5 % of VSS users and 4.9 % of USS users found the process unpleasant. Around 80 % of participants in both SS arms preferred taking a specimen at home rather than going to a health care professional for cervical screening. They also indicated a preference for using self-sampling kit to collect a sample for their next CC screening instead of visiting a health care professional (VSS 82.6 %, USS 89.1 %). Conclusion: Self-sampling appears to be a well-received alternative in women not attending routine CC screening programme.